(untitled) (Tribhuvan Journal, 2025)
God’s greatest creation is human life. In a sociological/cultural sense, one aspect is reproduction and food, and the other is education. In this case, food and reproduction are for the maintenance and transmission of culture. And in education, culture is preserved and transmitted. In the sociological and philosophical fields of equality of opportunity, socioeconomic status explains how and why the perception and experience of “equal opportunity” varies. The relationship between educational innovations and economic growth has become a popular topic in development economics, especially for developing countries seeking effective ways to increase economic growth by developing human capital. This research aims to understand the perspectives of different social groups on equal opportunity and the impact of socio-economic factors on it. This research primarily focuses on socio-economic factors and their impact on the perceptions of equal opportunity. The researcher used Google Scholar, JSTOR, ProQuest, and other academic search engines to locate relevant materials. Considering multiple studies, we focused on research that explored the illusion of equality, educational opportunities, and the socio-economic impact of equal educational opportunities. After setting these parameters and collecting relevant materials, the researcher used narrative strategies to synthesize them and clarify the findings. The more positive opportunities people have, the more likely they are to have higher income, education, employment level, and cultural/social capital. Members of disenfranchised/marginalized communities, and their socio structural barriers, are a review documenting the gap between policy and practice, which is persistent, as the practice of legally protecting people from discrimination does little to prevent the social, personal, and discrimination dysfunction it causes. The most obvious example of inequality is education, and within it, the multidimensional barriers of poverty, geographical remoteness, language, caste, disability, and social exclusion are prevalent. To assess the potential for equal opportunity, one must look beyond legally mandated non-discrimination policies to see whether the socio-economic and structural barriers that limit equal opportunity have been adequately addressed. All human beings are inherently valuable. Furthermore, equal opportunity depends on the social configuration and the people in it, and is therefore relative. This paper attempts to bring to the fore the complexities surrounding the notion of equality of opportunity in today’s world, which are shaped by the concerns highlighted.